Pemeriksaan Fungsi Penghidu Pada Rinitis Alergi - Eka Trie Sanggita, Vira (Jurnal Syntax Fusion, 2022)
Rhinitis is an inflammation of the lining membrane or nasal mucosa characterized by one or more symptoms such as sneezing, nasal congestion, itchy nose, and rhinorrhea or runny nose. Allergic rhinitis (hay fever) is clinically a disorder of nasal function resulting from an allergic reaction to allergen exposure through an inflammatory process mediated by specific IgE in the nasal mucosa. Allergic rhinitis can also be regarded as a chronic inflammatory disease of the upper respiratory tract with a reported prevalence of around 40% of the general population. The writing of this article was obtained from various sources in the form of scientific journals and guidelines for related institutions. Source searches were carried out on various online portals such as Medscape, NCBI Google Scholar and other health websites with the keyword “Allergic Rhinitis”. Allergic rhinitis is an inflammatory disease of the nasal mucosa caused by exposure to allergens. The prevalence of rhinitis in Indonesia is around 3-4% at the age of 6-7 years and 4-5% at the age of 13-14 years. Allergic rhinitis can occur when a person's immune system reacts to allergens such as dust mites, pollen, pet dander, mold spores, and insects such as cockroaches. Symptoms and signs that can occur in allergic rhinitis include runny nose, nasal congestion, itching in the nose, ears, throat, and palate, sneezing, coughing, headache, snoring due to nasal obstruction, and decreased sense of smell and taste. Allergic rhinitis that occurs in childhood worsens with age. The diagnosis of olfactory function in allergic rhinitis begins with anamnesis, physical examination and supporting examinations such as imaging and olfactory chemosensory examinations such as the UPSIT (University of Pennsylvania Small Identification) test, The Connectitut Chemosensory Clinical Research Center (CCCRC) test, and the "Sniffin Sticks test".